Reinstatement of Sigambra hanaokai (Kitamori, 1960) (Polychaeta, Pilargidae), with an overview of the literature on the genus - Nishi, Eijiroh; Tanaka, Katsuhiko; Fujioka, Yoshimi; Sato, Masanori (Zootaxa, 2007)
Sigambra hanaokai (Kitamori 1960), originally described from Japan, was regarded as a junior synonym of S. tentaculata (Treadwell 1941), described from the Northwestern Atlantic Ocean. We studied Japanese materials and compared them with a recent redescription of S. tentaculata and with S. phuketensis Licher and Westheide, 1997, another similar species. The validity of S. hanaokai is confirmed. In order to avoid any further confusion, we redescribe the species based on topotype specimens collected in Hiroshima, Seto Inland Sea, Japan, the type locality of the species. Additionally, we emphasize the differences between S. hanaokai and S. phuketensis, particularly in regard to the relative length of the median antenna. Lastly, we summarize the recent systematic status of all species of the genus, and provide a table summarizing taxonomic characters.